IMPLEMENTASI PROGRAM SMART CITY DI DINAS KOMUNIKASI DAN INFORMATIKA KOTA MANADO - MALUWU, KEVIN; TULUSAN, FEMMY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2021)
The purpose of this study was to determine the implementation of the smart city program at the ManadoCity Information and Comunication Department. This research uses descriptive qualitative researchmethods. Efforts or programs from the government in implementing the smart city of Manado City arerealized through several public service programs including the Smart Command Center (C3), the analysisand map-based portal (PANANDA), the latest online tax (PONTER) and Manado Alert 112 (MS112).However, the implementation of these programs is found not to be running optimally, several obstacles thathinder the running of the smart city program in the city of Manado, including the lack of human resourceswithin the Manado city government who are experts in the IT field with educational backgrounds in thefield of technology and education. information, this greatly influences the ability of the apparatus tounderstand and implement existing programs, becomes ineffective, then the public's ignorance of the smartcity program greatly affects the success of the smart city program in the city of Manado, then because of thelarge budget in meeting the needs for information technology infrastructure, the implementation of thesmart city program has not been able to cover all the agencies, only a few agencies have been able to runthe programKeywords : Program Implementation, Smart City